Comparative Analysis of Gene Expression Profiles in the Adipose Tissue of Obese Adult Mice With Rapid Infantile Growth After Undernourishment In Utero - Suzuki, Misako; Kohmura-Kobayashi, Yukiko; Ueda, Megumi; Furuta-Isomura, Naomi; Matsumoto, Masako; Oda, Tomoaki; Kawai, Kenta; Itoh, Toshiya; Matsuya, Madoka; Narumi, Megumi; Tamura, Naoaki; Uchida, Toshiyuki; et al. (Frontiers in Endocrinology, 2022)
Rapid infantile growth (RG) markedly increases the risk of obesity and metabolic disorders in adulthood, particularly among neonates born small. To elucidate the molecular mechanisms by which RG following undernourishment in utero (UN) contributes to the deterioration of adult fat deposition, we developed a UN mouse model using maternal energy restriction, followed by RG achieved by adjustments to 4 pups per litter soon after birth. A high-fat diet (HFD) was fed to weaned pups treated or not (Veh) with tauroursodeoxycholic acid (TU). UN-RG pups showed the deterioration of diet-induced obesity and fat deposition, which was ameliorated by TU. We performed a microarray analysis of epididymal adipose tissue and two gene enrichment analyses (NN-Veh vs UN-RG-Veh and UN-RG-Veh vs UN-RG-TU). The results obtained identified 4 common gene ontologies (GO) terms of inflammatory pathways. In addition to the inflammatory characteristics of 4 GO terms, the results of heatmap and principal component analyses of the representative genes from 4 GO terms, genes of interest (GOI; Saa3, Ubd, S100a8, Hpx, Casp1, Agt, Ptgs2) selected from the 4 GO terms, and immunohistochemistry of macrophages collectively suggested the critical involvement of inflammation in the regulation of fat deposition in the responses to UN and TU. Therefore, the present results support the ‘Developmental Origins of Metaflammation’, the last word of which was recently proposed by the concept of metabolic disorders induced by low-grade systemic inflammation.